The aesthetic sequence of the image of war Hani Al Raheb’s novel "A Thousand and Two Nights" - إسماعیل دیما; فاخر ميا; محمد مروشيه (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Each picture has its own aesthetic formation, which distinguishes it from others through the energy it releases and that fascinates the recipient and draws him/her to follow its. dimensions with caution. The war image is like other images that are embodied by forming an effect that goes beyond the dimensions of the image itself to another image within the text.